Mergers and acquisitions in the context of the COVID-19 pandemic and Russian-Ukrainian war - Joanna Toborek- Mazur (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2022)
The pressure of competition resulting from changes in the markets caused by the COVID-19 pandemic and the outbreak of war in Ukraine, forces entrepreneurs to revise the direction of business development. The difficulties associated with organic growth make some of them interested in the transactional market, where there is the possibility of concluding mergers and acquisitions. This pressure is dictated by the volatility of economic factors. Some of the investors must act decisively not only to avoid the risk of losing financial liquidity, but above all to find a strategic partner that will allow them to maintain an optimal competitive position and survive in a turbulent environment. Being aware of the risks, the owners and managerial staff must have a development plan assuming acquiring new sales markets or strengthening their position. In the context of the multiplicity of various adverse economic events in 2022, mergers and acquisitions may turn out to be the right business solution.